Energy Consumption, Trade Openness and Economic Growth: Empirical Evidence from Nigeria - Akinwale, Yusuf Opeyemi (International Journal of Energy Economics and Policy, 2021)
This paper explores the link between energy consumption, trade openness and economic growth in Nigeria between 1971 and 2015 using Vector error correction model (VECM). The result of Johansen co-integration test shows that the three series are co-integrated, hence long-run relationship was established among them. Causality analysis in VECM shows that there is a long run causality from economic growth and trade openness to energy consumption as well as from economic growth and energy consumption to trade openness. The results of the short run causality indicate the Granger causality from economic growth to trade openness only. These outcomes suggest that trade openness could be boosted by improving production in all sectors of the economy and not the other way round. Also, decisive improvement in economic activities would lead to increase in energy use in the country as the size of the current energy consumption is too weak to cause economic expansion in Nigeria. Furthermore, due to the huge energy gap between demand and supply, Nigerian government should utilise the low carbon energy options towards a sustainable economic growth trajectory. Keywords: Economic growth; Vector error correction model; Energy consumption; Co-integration; Trade openness JEL Classifications: C01, F14, F41, Q43 DOI: https://doi.org/10.32479/ijeep.11617